2016
DOI: 10.4081/pr.2016.6632
|View full text |Cite
|
Sign up to set email alerts
|

Post Discharge Formula Fortification of Maternal Human Milk of Very Low Birth Weight Preterm Infants: an Introduction of a Feeding Protocol in a University Hospital

Abstract: The objective of this study is to determine the growth parameters and nutritional biochemical markers and complications of fortification of human milk by post discharge formula of preterm very low birth weight newborns (VLBW). Fifty preterm infants less than 37 weeks with weight less than 1500 g were enrolled in the study. They received parental nutrition and feeding according to our protocol. When enteral feeding reached 100 cc/kg/day, infants were randomized into two groups: group I, Cases, n=25, where post … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Fortification of mother's milk was introduced in the 1990s to improve growth in VPI while supporting breastfeeding at the same time [18]. Arslanoglu et al [19] showed that protein enrichment increased growth in VPI up to 5 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…Fortification of mother's milk was introduced in the 1990s to improve growth in VPI while supporting breastfeeding at the same time [18]. Arslanoglu et al [19] showed that protein enrichment increased growth in VPI up to 5 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…The composition of the formulations used in the study was similar to other products available in the country (eTable 5 in Supplement 2). In contrast to the weight gain, the weekly length gain and head circumference growth in this study were comparable with that in the previous studies …”
Section: Discussionmentioning
confidence: 87%
“…In contrast to the weight gain, the weekly length gain and head circumference growth in this study were comparable with that in the previous studies. 10,20,21 Neonates in the PTF group had a significantly lower incidence of feed intolerance during the hospital stay (eTable 4 in Supplement 2). The proportion of neonates having 1 or more episodes of feed intolerance was also lower in the PTF group: 3% (n = 2) vs 14% (n = 9) (eTable 4 in Supplement 2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Breast milk alone is insufficient to support the growth of premature VLBWIs [ 14 ], but fortification improves their growth [ 16 ]. However, human milk fortifiers were not approved by the Jordan Food and Drug Administration; instead, breast milk was fortified using premature discharge formula, a practice documented before in our region [ 17 ]. Fortification was started once the infants reached full feeds.…”
Section: Discussionmentioning
confidence: 99%